2022
DOI: 10.21831/jk.v10i1.47542
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise model and limb length on the accuracy of kuda service in sepak takraw

Abstract: This study aims: (1) the differences in the effect of static and dynamic targets on the accuracy of kuda service; (2) the effect long and short limb on the accuracy of kuda service; and (3) the interaction between of static, dynamic targets and limb lengths (long and short) on the accuracy of kuda service by sepak takraw male players. This study method was an experimental research factorial design. The population was 32 athletes from PSTI Club Sleman and Bantul. 24 samples were chosen based on Slovin formula u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Subsequent research found a significant interaction between static, dynamic, and limb length targets (long and short) on the accuracy of horse serves in male sepak takraw players (Marpaung et al, 2022). The sepak takraw first ball training method is very important in the game of sepak takraw, especially in mastering the first ball (Maseleno & Hasan, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research found a significant interaction between static, dynamic, and limb length targets (long and short) on the accuracy of horse serves in male sepak takraw players (Marpaung et al, 2022). The sepak takraw first ball training method is very important in the game of sepak takraw, especially in mastering the first ball (Maseleno & Hasan, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Game modifications are expected to provide equal opportunities for all children, so the game is not only monopolized by more capable children. Based on the description above, it is necessary to develop a model for the game of sepak takraw as learning physical education for elementary school children high class Based on the results of media experts and expert sepak takraw practitioners that the development of this takraw is very valid in terms of product convenience and product effectiveness (Mariadi et al, 2021); (Marpaung et al, 2022). Meanwhile, based on the results of responses from takraw ball users who developed very high results in developing takraw balls.…”
Section: Resultsmentioning
confidence: 99%
“…Melalui pendidikan manusia mendapatkan pengetahuan dan keterampilan untuk menyerap, menilai dan mengembangkan ilmu yang bermanfaat dalam kehidupannya (Pratama & Wiyaka, 2021). Selain itu pendidikan juga berfungsi sebagai sarana manusia untuk mengembangkan potensi dirinya (Harahap & Sinulingga, 2021) serta peradaban bangsa yang bermartabat dalam rangka mencerdaskan kehidupan bangsa, bertujuan untuk berkembangnya potensipeserta didik agar menjadi manusia beriman dan bertaqwa kepada Tuhan Yang Maha Esa,berakhlak mulia, sehat, berilmu cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab (Marpaung & Siregar, 2022). Berdasarkan hasil observasi dan pengamatan serta wawancara dengan guru penjas kelas V di SDN 016536 Bagan, Asahan peneliti melihat bahwa dalam pelaksanaan kegiatan pembelajaran pendidikan jasmani pada materi permainan Bola Kasti teknik dasar melempar bola siswa kurang dapat melakukan teknik dasar tersebut dengan baik dan merasa kesulitan dalam melakukan teknik dasar tersebut, sehingga hasil belajar yang diperoleh siswa kurang maksimal (Aristiyanto et al, 2020).…”
Section: Pendahuluanunclassified